Information value of echocardiography in inferior myocardial infarction at different stages of observation - Endge G. Akramova; Evgeniia V. Vlasova; Anatoly A. Saveliev; Elvira B. Zakirova (Клиническая практика, 2024)
BACKGROUND: A wide range of indicators and examination methods in acute myocardial infarction complicates their interpretation, affecting the objectivity and reliability of the final conclusions. In this situation, the results of a multivariate mathematical analysis can serve as a guide, allowing one to determine statistically significant indicators and establish a range of critical values for a particular case.